2020
DOI: 10.1038/s42003-020-1078-y
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping analysis reveals new variants and accelerated evolution of Clostridioides difficile toxin B

Abstract: Clostridioides difficile toxins (TcdA and TcdB) are major exotoxins responsible for C. difficile infection (CDI) associated diseases. The previously reported TcdB variants showed distinct biological features, immunoactivities, and potential pathogenicity in disease progression. Here, we performed global comparisons of amino acid sequences of both TcdA and TcdB from 3,269 C. difficile genomes and clustered them according to the evolutionary relatedness. We found that TcdB was much diverse and could be divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 61 publications
5
70
0
Order By: Relevance
“…We have previously demonstrated that common laboratory diagnostic assays may be challenged by changes in the PaLoc of C-I strains 21 . The same might be true for monoclonal antibody-based treatments for CDI such as bezlotoxumab, known to have distinct neutralizing activities against different TcdB subtypes 57 .…”
Section: Discussionmentioning
confidence: 94%
“…We have previously demonstrated that common laboratory diagnostic assays may be challenged by changes in the PaLoc of C-I strains 21 . The same might be true for monoclonal antibody-based treatments for CDI such as bezlotoxumab, known to have distinct neutralizing activities against different TcdB subtypes 57 .…”
Section: Discussionmentioning
confidence: 94%
“…TcdB1-4 are major variants that together were found in over 99.6% of the pathogenic C . difficile strains [ 15 ]. To determine the functional contribution of CSPG4 and FZD1/2/7 in mediating the toxin entry of these TcdB variants into host cells, we compared the activities of TcdB variants using the standard cytopathic cell-rounding assay on the HeLa-Cas9 (parental cell line, referred to as the wildtype (WT) HeLa thereafter) cells versus CSPG4 knockout ( CSPG4 –/– ) and FZD1/2/7 knockout ( FZD1/2/7 –/– ) HeLa cells, which were generated previously via CRISPR/Cas9 approach [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The high diversity of receptor preference may potentially benefit the pathogen on its host adaption. Although the driven force remains unknown, TcdB appears to be rapidly evolving [ 15 ] which may provide flexibility to attack a wide range of host cells and tissues. On the other hand, natural toxin variants provide optimal tools to study their contributions to disease progressions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations